Pension funding and individual accounts in economies with life-cyclers and myopes - Hans Fehr; Fabian Kindermann (Center for Economic Studies and ifo Institute (CESifo), 2009)
The present paper studies the growth and efficiency consequences of pension funding with individual retirement accounts in a general equilibrium overlapping generations model with idiosyncratic lifespan and labor income uncertainty. We distinguish between economies with rational and hyperbolic consumers and compare the consequences of voluntary and mandatory retirement plans. Three major findings are derived in our study: First, we quantify the commitment effect of social security for myopic individuals by roughly 1 percent of aggregate resources. It is possible to recapture this commitment technology in IRAs, if those are annuitized. Second, despite the fact that our consumers have an operative bequest motive, the welfare gain from the (implicit) longevity insurance of the pension system is significant and amounts to roughly 0.5 percent of aggregate resources. However, mandatory annuitization reduces unintended bequests so that future generations are significantly hurt. Finally, our results highlight the importance of liquidity effects for social security analysis. These efficiency gains are only attainable if accounts are voluntary and not mandatory.
Keywords: H55; J26; 330; individual retirement accounts; annuities; stochastic general equilibrium; hyperbolic consumers; Alterssicherung; Rentenfinanzierung; Private Rentenversicherung; Konsumentenverhalten; Zeitpräferenz; Versicherungspflicht; Wohlfahrtseffekt; Allgemeines Gleichgewicht; Overlapping Generations; Theorie